Relationship Between First 24-h Mean Body Temperature and Clinical Outcomes of Post-cardiac Surgery Patients - Xu, Fei; Zhang, Cheng; Liu, Chao; Bi, Siwei; Gu, Jun (Frontiers in Cardiovascular Medicine, 2021)
Background: This study was aimed to investigate the relationship between first 24-h mean body temperature and clinical outcomes of post cardiac surgery patients admitted to intensive care unit (ICU) in a large public clinical database. Methods: This is a retrospectively observational research of MIMIC III dataset, a total of 6,122 patients included. Patients were divided into 3 groups according to the distribution of body temperature. Multivariate cox analysis and logistic regression analysis were used to investigate the association between abnormal temperature, and clinical outcomes. Results: Hypothermia (<36°C) significantly associated with increasing in-hospital mortality (HR 1.665, 95%CI 1.218–2.276; p = 0.001), 1-year mortality (HR 1.537, 95% CI 1.205–1.961; p = 0.001), 28-day mortality (HR 1.518, 95% CI 1.14–2.021; p = 0.004), and 90-day mortality (HR 1.491, 95% CI 1.144–1.943; p = 0.003). No statistical differences were observed between short-term or long-term mortality and hyperthermia (>38°C). Hyperthermia was related to the extended length of ICU stay (p < 0.001), and hospital stay (p < 0.001). Conclusion: Hypothermia within 24h after ICU admission was associated with the increased mortality of post cardiac surgery patients. Enhanced monitoring of body temperature within 24h after cardiac surgery should be taken into account for improving clinical outcomes.